The Role of The Government in The Recognition of Customary Rights to Achieve Economic Development of Customary Law Communities - Wulansari, RR. Catharina Dewi; APHA, Journal Manager (Jurnal Hukum Adat Indonesia, 2017)
Every State wants a condition in which the people have a prominent level of welfare and prosperity, because that condition can reflect how a state has been successful in carrying out its development. The existence of development that can lead to prominent level of welfare and prosperity, certainly, shows the success of a state in achieving the state's goals. But in practice it is often found that the people of a state do not have a prominent level of welfare and prosperity due to the unprotected rights of the people. The lack protection rights of the people are one form of social problems; which of course requires a very fast handling. Therefore, in general, every state tries, so that the protection rights of the people can be fulfilled. Similarly, for the state of Indonesia, the protection of communal customderived land rights (ulayat rights) of indigenous peoples is one of the tasks that must be fulfilled by the government. The effort is not easy; therefore, needs a thorough study to overcome the problem. The method used in this research is a normative juridical method. The results of the study, indicate the role of government in regulating the recognition forms of the rights of indigenous peoples, especially, communal custom-derived land rights of indigenous people. In addition, there are various substances of legislation that must be regulated in order to recognize communal custom-derived land rights of indigenous people such as how to recognize indigenous peoples, their recognition procedures, indigenous peoples' obligations, and dispute resolution mechanisms. Finally, regulation about recognition of indigenous peoples is expected to have an impact on the economic development of indigenous peoples itself.